Air-permeable electrode for highly sensitive and noninvasive glucose monitoring enabled by graphene fiber fabrics. (March 2022) - Cai, Shengying; Xu, Changshun; Jiang, Danfeng; Yuan, Meiling; Zhang, Qingwen; Li, Zhaoling; Wang, Yi
Abstract: Developing wearable and noninvasive electrochemical devices for glucose monitoring is desirable for diabetes diagnostics and management. However, the adoptions are restricted by their poor reliability due to diluted glucose densities in commonly-used body fluids while lack of highly sensitive electrodes. Graphene fiber fabric, which is macroscopically paper-like and assembled by wet-fused graphene fibers, provides excellent electrical and mechanical properties as well as penetration paths for liquids, showing great potentials for electrochemical monitoring. Additionally, the graphene fiber fabric as a sensing patch provides excellent air-permeability which is necessary for wearing comfort but has rarely been addressed. As a result, the Prussian blue-decorated graphene fiber fabric exhibits a high electrochemical sensitivity to hydrogen peroxide (7298.7 μA mM −1 cm −2 ). After being modified by glucose oxidase and chitosan, it delivers both high selectivity and electrochemical sensitivity to glucose (1539.53 μA mM −1 cm −2 in the concentration range of 2–220 μM, and 948.48 μA mM −1 cm −2 in the concentration range of 220–650 μM). We ascribe these performances to high-speed transfer paths for electrons and electrolytes in resultant electrodes. Additionally, the spontaneous absorption of body liquids by graphene fiber fabric after deposition of hydrophilic Prussian blue improves the utilization of active materials. Finally, the graphene fiber fabric used as a dry sensing patch was applied on human skin for the in vivo noninvasive glucose monitoring with the reverse iontophoresis (RI) technology, which showed good correlation to glucose levels measured by a commercial finger-prick glucometer. Graphical Abstract: The air-permeable electrode consisted of wet-fused graphene fibers and Prussian blue enables highly sensitive detection of glucose after being modified by glucose oxidase and chitosan. It is applied as a dry sensing patch with the integration of reverse iontophoresis technology on human skin for noninvasive glucose monitoring, showing high correlation with the blood glucose level measured by a commercial finger-prick glucometer. ga1 Highlights: A highly sensitive (1539.53 μA mM −1 cm −2 ) and selective electrode for noninvasive glucose monitoring is realized. A 3-dimensional electrode which can directly load enzymes and uptake body fluids for glucose sensing is realized. Air-permeability and flexibility of electrodes which are necessary for wearing comfort have been achieved. In vivo noninvasive glucose measurements which show good correlation to blood glucose levels is achieved.